Resilience of Chinese Reverted Muslim in Facing Double Minorities Status: A Study in Malaysia Context - Yu, Ta Honn; Bt Basiron, Bushrah (Borneo International Journal of Islamic Studies, 2022)
Resilience is one of the important constructs in human positive functioning, especially in facing the challenges from various walks of life. Chinese Reverted Muslim (CRM) in Malaysia is a minority group in both the population of Malaysian Chinese as well as in the Muslim community, which falls under the category of double minorities. In the need of facing chronic stressors such as discrimination, racism, and prejudice as double minorities, thus to be in the double minorities status (DMS), CRM requires a great deal resilience to overcome all these negative circumstances. Past studies regarding CRM is of little, especially in Malaysia context. Globally research also focused more on Chinese Muslim but not CRM. The trace of literature on resilience in CRM also cannot be found in either overseas or local research. Malaysian unique polarized racial structure and history provides a worthy paradigm in studying the population of DMS also probe on the strength and resilience from the religious and cultural perspective. Numerous CRM national exemplary from various society background had been exercising the resilience throughout the years since the independence of Malaysia in the year of 1957. By understanding the mechanism of resilience behind CRM dealing with DMS, it will be helpful in personality building especially in resilience for the oppressed groups.